Dynamic vulcanization of natural rubber/high-density polyethylene blends: Effect of compatibilization, blend ratio and curing system - Charoen Nakason (2018)
Thermoplastic vulcanizates (TPVs) based on NR/HDPE blends with various types of blend compatibilizers were prepared. It was found that TPVs with phenolic resin (i.e., SP-1045 and HRJ-10518) compatibilizers showed higher tensile strength, elongation at break and tendency to recover from prolonged extension than those of the TPV without a compatibilizer. This may be attributed to Chroman ring structures from the reaction of NR and phenolic molecules. The TPVs with modified phenolic resins (PhSP-PE and PhHRJ-PE) showed higher tensile strength and elongation at break than those of the TPVs with un-modified phenolic rein and without a compatibilizer. A reaction took place through trace quantities of un-saturation in the HDPE molecules and methylol groups in the phenolic molecules. Also, the remaining methylol groups in the phenolic molecules were capable of reacting with NR molecules and produced a linkage between NR and HDPE molecules. Therefore, it was found that the TPV with PhHRJ-PE gave the highest tensile strength and elongation at break. Increasing the content of the NR gave an increased trend of elongation at break but decreasing trends in permanent set (expressed as tension set), tensile strength and hardness. Various vulcanization systems were also used to prepare the TPV, with a mixed curing system showing the highest shear stress and tensile strength, whilst the sulphur curing system gave the lowest values, and the peroxide curing system exhibited intermediate values. © 2006 Elsevier Ltd. All rights reserved.